PENGEMBANGAN BLOG SEDERHANA WWW.KENNEDEUTSCH.BLOGSPOT.COM SEBAGAI MEDIA AJAR PADA KETERAMPILAN BERBICARA BAHASA JERMAN SMA NEGERI 1 TARIK SIDOARJO KELAS X SEMESTER 1 - Faradila, Deviga Hylda; Julaikah, Dwi Imroatu (LATERNE, 2022)
In the modern and all-digital era as it is today, technology is overgrowing. Starting from work Affairs to the educational environment is also not spared from the reach of technology. Blog page www.kennedeutsch.blogspot.com is a blog that contains German material with the theme of self-identity contained in Class X Semester 1. The author developed the blog page using the development method by Bergman and Moore (1990). This development Model includes six stages 1) Analysis, 2) design, 3) development, 4) production, 5) merging, 6) and validation. Based on interviews with teachers teaching subjects in SMA Negeri 1 Tarik Sidoarjo concluded that students experience some obstacles that cause low speaking skills, namely 1) the existence of a sense of self-confidence, 2) minimal vocabulary, 3) limited hours of learning. Therefore the blog page www.kennedeutsch.blogspot.com developed to support the needs of students in learning German independently that can be used anytime and anywhere. Based on the needs analysis carried out on October 26, 2021, online through google Forms, 90.1% of students need a variety of practical and flexible learning media to learn to speak independently. Results of validation conducted on March 29, 2022 by Nur Nihayati, S.Pd. as a teacher German subjects in SMAN 1 Tarik Sidoarjo. The material or content analyzed is said to be appropriate and suitable for use as a medium of German language learning in Class X semester one based on the 2013 curriculum. Based on that, the formulation of the problem contained in the writing of this article is how the development of the blog as a teaching medium for German-speaking skills class X IPA 3 Semester one. Moreover, this article aims to describe the development of the blog as a teaching medium for German-speaking skills class X IPA 3 Semester